English Teachers’ Strategies in Teaching Preschool Students Using The Montessori Method: A Case Study at Bale Anak Lombok Montessori School Futura Indonesia - Dwi Rina Apriliana; Untung Waluyo; Henny Soepriyanti; Hartati Suryaningsih (Jurnal Ilmiah Profesi Pendidikan, 2024)
The increasing significance of English as a global lingua franca underscores the need for effective early language education strategies. This study examines English teachers' strategies in implementing the Montessori method at Bale Anak Lombok Montessori School to enhance pre-schoolers' vocabulary acquisition and address pedagogical challenges. Employing a qualitative descriptive case study design, data were collected through non-participatory classroom observations, semi-structured interviews with two teachers, and document analysis. Findings reveal that the Three-Period Lesson—a core Montessori strategy—was pivotal in introducing vocabulary through structured progression, using tangible materials and interactive activities to foster engagement and retention. Supplementary strategies included storytelling, songs with movements, and gamified activities, which addressed young learners' developmental needs and short attention spans. Articulation challenges were mitigated through repetition and individualized observation, while parent involvement reinforced learning consistency at home. The study highlights the Montessori method's alignment with constructivist principles, emphasizing hands-on, child-centered learning that supports holistic development. These findings suggest that integrating interactive, multisensory approaches can significantly enhance early language education. Implications include the need for professional training to adapt Montessori principles effectively and for future research to explore their application in diverse educational and cultural contexts.